Recent Advances in Diversity-Oriented Polymerization Using Cu-Catalyzed Multicomponent Reactions - Lee, In Hwan; Bang, Ki Taek; Yang, Hee Seong; Choi, Tae Lim (Macromolecular Rapid Communications, 2022)
Diversification of polymer structures is important for imparting various properties and functions to polymers, so as to realize novel applications of these polymers. In this regard, diversity-oriented polymerization (DOP) is a powerful synthetic strategy for producing diverse and complex polymer structures. Multicomponent polymerization (MCP) is a key method for realizing DOP owing to its combinatorial features and high efficiency. Among the MCP methods, Cu-catalyzed MCP (Cu-MCP) has recently paved the way for DOP by overcoming the synthetic challenges of the previous MCP methods. Here the emergence and progress of Cu-MCP, its current challenges, and future perspectives are discussed.
Keywords: Cu-catalyzed multicomponent polymerization; Cu-catalyzed multicomponent reaction; Diversity-oriented polymerization; Multicomponents; Novel applications; Polymer structure; Polymerization method; Property; Synthetic strategies; Catalysis; Polymerization; Polymers; Cu-catalyzed multicomponent polymerization; Cu-catalyzed multicomponent reaction; diversity-oriented polymerization